METODE PENGAJARAN TAUHID NABI IBRAHIM AS - Fahri, Muhammad (ATTA`DIB, 2016)
Tawhid as the basis of Islamic teaching and education is the most important substances in educating generations of Muslims. Al Quran as a guidance for Muslims has great concern about the substance of tawhid and its teaching methods. One is story of the prophet Ibrahim who taught his followers about tawhid to Allah This study will reveal the tawhid teaching methods of prophet Ibrahim in surah al Anbiyaa verses 51-70. This study is qualitative, which aims to find and explore information about the interpretation of the Qur'an surah al Anbiyaa verses 51-70 with the relevant references. The method used in this study is maudhu'i interpretation method, that is by examining verses of the various aspects of it, and doing the analysis based on the true science that is used to describe the subject matter, so as to understand the problem and purpose of verses easily. In this case focused on evaluating one element of education, it’s the teaching methods.The research findings of studies on the substance and tawhid teaching methods of prophet Ibrahim can be used as a reference and applied in the teaching of Islam, especially the tawhid teaching in educational institutions. Thus the purpose of teaching can be achieved well.